Model Pengembangan Karakter Berbasis Mind Mapping Pada Anak Usia Dini - Masganti Sit; Nurmawati , (UMSU, 2019)
The aims of this research are: 1) find out the steps of mind mapping-based character development for early childhood, 2) steps to implement mind mapping-based character development in early childhood, 3) increase the character of children after the application of mind mapping based character development models in early childhood, and 4) the response of teachers and parents to the use of mind mapping-based character development models in early childhood. This research uses research and development methods. The results of this research show: 1) The steps of character development based on mind mapping begin with the preparation of the Teacher's Guide Book and Student Worksheets and are validated by first time education material experts, graphic design, and the Indonesian liguist in a very valid category, 2) the steps of implementing the model consisting of preparation, implementation and evaluation, 3) Test results The model shows that the use of mind mapping-based character development models in early childhood can develop children's character significantly with thit 17.038> from 2.46 at 95% significance level, and 4) teachers and parents assess this model is suitable for developing children's character